Cardiovascular Surgical Emergencies in France, before, during and after the First Lockdown for COVID-19 in 2020: A Comparative Nationwide Retrospective Cohort Study - Anna Baudry (MDPI AG, 2021)
Background: There are still gaps regarding the impact of the nationwide lockdown on non-COVID-19 emergency hospitalizations. This study aims to describe the trends in hospitalizations for cardiovascular surgical emergencies in France, before, during and after the first lockdown. Materials and Methods: All adults admitted for mechanical complications of myocardial infarction (MI), aortic dissection, aortic aneurysm rupture, acute and critical limb ischemia, circulatory assistance, heart transplantation and major amputation were included. This retrospective cohort study used the French National Hospital Discharge database. The numbers of hospitalizations per month in 2020 were compared to the previous three years. Results: From January to September 2020, 94,408 cases of the studied conditions were reported versus 103,126 in the same period in 2019 (−8.5%). There was a deep drop in most conditions during the lockdown, except for circulatory assistance, which increased. After the lockdown, mechanical complications of MI and aortic aneurysm rupture increased, and cardiac transplantations declined compared with previous years. Conclusion: We confirmed a deep drop in most cardiovascular surgical emergencies during the lockdown. The post-lockdown period was characterized by a small over-recovery for mechanical complications of MI and aortic aneurysm rupture, suggesting that many patients were able to access surgery after the lockdown.